The Relationship Between Public Debt and Inflation in Developing Countries: Empirical Evidence Based on Difference Panel GMM - Bon, Nguyen Van (Asian Journal of Empirical Research, 2015)
High inflation is considered to be an adverse factor to economic growth in developing countries. High economic growth at a stably low inflation is one of major objectives for most of governments worldwide. However, most of developing countries have to borrow debts to finance budget deficits and to promote economic growth. The paper empirically investigates the relationship between public debt and inflation for 60 developing countries in Asia, Latin America and Africa over the period 1990 – 2014 via the estimation method of difference panel GMM Arellano-Bond. The estimated results show that in the direction from public debt to inflation, public debt has a significantly positive effect on inflation while in the opposite direction, inflation has a significantly negative effect on public debt. Furthermore, the study also found the significant determinants of public debt and inflation in developing countries of Asia, Latin America and Africa. These results suggest some important policy implications for governments in developing countries.